2016
DOI: 10.29133/yyutbd.258569
|View full text |Cite
|
Sign up to set email alerts
|

İşlenen ve İşlenmeyen Arazilerde Bazı Ağır Metallerin Toprak Profili Boyunca Değişiminin Değerlendirilmesi

Abstract: Özet: Bu araştırma, işlenen ve işlenmeyen toprakların bazı ağır metal içeriklerinin toprak profil derinliğindeki değişimini incelemek amacıyla yürütülmüştür. Çalışma, alüviyal ana materyal üzerinde oluşmuş 12 tanesi işlenen ve 12'si işlenmeyen arazi olmak üzere toplam 24 profilde ve 0-30, 30-60 ve 60-90 tabakalarından alınan toprak örnekleri üzerinde yapılmıştır. Toprak örneklerinde tane büyüklük dağılımı, organik madde içeriği, kireç, toprak reaksiyonu, demir, bakır çinko, nikel, kurşun ve kadmiyum analizleri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, positive relationships were found between both Cr content and Ni (p<0.01) concentration and between Pb content and Zn (p<0.01) concentration. Many researchers have obtained similar results in correlation analysis between OM, pH, lime and soil particle distribution with heavy metal content of soils (Demir et al, 2016;Özyazıcı et al, 2017;Tang et al, 2018). On the other hand, some researchers (Tume et al, 2006;Nizami and Rehman, 2018) reported that there was no relationship between pH and OM content of soils and heavy metal contents.…”
Section: Correlation Analysismentioning
confidence: 80%
“…In addition, positive relationships were found between both Cr content and Ni (p<0.01) concentration and between Pb content and Zn (p<0.01) concentration. Many researchers have obtained similar results in correlation analysis between OM, pH, lime and soil particle distribution with heavy metal content of soils (Demir et al, 2016;Özyazıcı et al, 2017;Tang et al, 2018). On the other hand, some researchers (Tume et al, 2006;Nizami and Rehman, 2018) reported that there was no relationship between pH and OM content of soils and heavy metal contents.…”
Section: Correlation Analysismentioning
confidence: 80%